Case report: Successful treatment of advanced pulmonary sarcomatoid carcinoma with BUBIB-ALK rearrangement and KRAS G12C mutation by sintilimab combined with anlotinib - Huang, Nana; Qu, Tianhao; Zhang, Chunxia; Li, Jia (Frontiers in Oncology, 2024)
Pulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive subtype of non-small cell lung cancer (NSCLC) that is characterized by poor differentiation and invasiveness. According to the World Health Organization, PSC exhibits sarcoma or sarcomatoid differentiation and typically presents with an insidious onset, lacking specific symptoms and signs. It is associated with high malignancy, early metastasis, short survival time, and a poor prognosis. Treatment for PSC follows a similar approach to NSCLC; however, it presents significant challenges due to its high resistance to chemotherapy. Previous research has demonstrated the coexistence of two or more target mutations in PSC, and the presence of multiple mutations is correlated with higher mortality rates compared to single mutations. This is supported by our case study of a male patient with advanced BUBIB-ALK rearrangement and KRAS G12C missense mutation. There is currently no standard treatment protocol available for patients with this condition. The patient showed rapid progression after 1 month of alectinib treatment and was intolerant to paclitaxel + cisplatin chemotherapy. Following this, successful disease control was achieved with a combination therapy of sintilimab and anlotinib. The patient achieved a progression-free survival (PFS) of over 20 months, and long-term follow-up is still ongoing for the patient. Based on our clinical experience, the combination of anlotinib and programmed death-1 (PD-1) inhibitors may be a promising strategy for PSC patients, particularly those with multi-target mutations who do not respond to ALK-TKI and are resistant to chemotherapy.